Motivation and Performance in Industrial Selling: Present Knowledge and Needed Research - Walker, Orville C.; Churchill, Gilbert A.; Ford, Neil M. (Journal of Marketing Research, 1977)
This position paper argues that current knowledge of the determinants of motivation and performance in industrial selling is woefully inadequate. As a first step toward improving this situation, the authors offer a conceptual model which identifies a set of individual, interpersonal, organizational, and environmental variables that may influence a salesman's motivation and job performance. The model incorporates many constructs and research findings from industrial psychology and other disciplines, but its primary purpose is to provide a conceptual framework and some specific hypotheses to help guide future empirical research in sales management.